Principles of biophotonics. - Popescu, Gabriel, 1971- (IOP (Series). Release 6., 2018)
Principles of Biophotonics: Linear systems and the Fourier transform in optics aims to teach students, instructors and professionals the basis of optical techniques for biological investigation. It is a textbook for experimentalists who are active at the interface between biology, medicine and optics (i.e. biological optics, biomedical optics, biophotonics, etc), and presents the unifying optics principles employed in this broad and interdisciplinary field. In the format of a classical textbook, this work contains both the underlying theory of biological optics and applications to real laboratory problems via exercises and homework. While keeping mathematical rigor, the theory is presented with stress on the physical phenomena and heavy use of the linear systems approach and frequency domain representation. The book emphasizes the similarity between various techniques, thus reducing the number of governing concepts as much as possible. Part of IPEM-IOP Series in Physics and Engineering in Medicine and Biology.